THE IMPACT OF THE INFORMATION INFRASTRUCTURE ON THE REGION COMPETITIVENESS - T. R. Shakirov (Финансы: теория и практика)
With the development of the fifth technological tenor and emerging elements of the sixth tenor in a number of leading economies the role of information as a production factor is increasing dramatically. In this regard, the competitiveness of the regional economy today is largely determined by the level of its IT penetration. The growth drivers in the innovation economy of a region that define its industrial structure, are high-tech industries such as software development, R&D as well as all high-tech productions that form the basis of the new tenor of technology. The paper examines the impact of the development level of the information infrastructure on the regional competitiveness. It proves that the investment attractiveness is highly dependent on how developed is the information infrastructure of a region. The international experience of regional informatization is considered. A particular stress is laid on the need to invest into the information infrastructure of Russian regions to create a favorable investment climate. The conclusions made in the paper are, according to the author, particularly important in the context of the trend for import substitution. The results of the research can be used to finalize strategic programs, such as “North-West 2030”, and taken into account by specialized executive bodies, particularly the Russian Ministry of Communications, as strategic priorities for the development of the regional infrastructure.